The Effect of Smartphone Addiction on Phubbing Behavior Among Students of the Faculty of Ushuluddin and Dakwah at IAIN Bone - indah, Andi tri batari; Syahril, Syahril; Asry, Nahdatunnisa; Rosniar, Rosniar (State Islamic Institute of Bone, Indonesia, 2025)
This research discusses the influence of smartphone addiction on phubbing behavior of students of the Faculty of Ushuluddin and Da'wah IAIN Bone. The subject matter is whether smartphone addiction has a contribution in influencing the emergence of phubbing behavior in students of the Faculty of Ushuluddin and Da'wah IAIN Bone. The method used in this research is a quantitative method of correlational type. Respondents in this study amounted to 202 active students of the Faculty of Ushuluddin and Da'wah IAIN Bone class of 2019-2022 with data collection techniques using random sampling. Data analysis in this study used simple linear regression test. The results showed that there is a positive influence of smartphone addiction on phubbing behavior in students (B = 0.507) with a significant level of p = 0.000, which means there is a positive influence of smartphone addiction on phubbing behavior in students. So, it can be explained that excessive use of smartphones that cause addiction can trigger the emergence of phubbing behavior in students. Based on the results of the study, smartphone addiction has a contribution of 17.9% to phubbing behavior.